Marine sediment quality at coastal monitoring stations in Vietnam 2016–2020 - Duong, Thanh Nghi; Le, Van Nam; Nguyen Thi , Thu Ha; Nguyen Thi, Mai Luu; Dinh, Hai Ngoc; Dang, Hoai Nhon; Hoang, Thi Chien; Pham Thi, Minh Hanh; Vu, Tuan Anh (Vietnam Journal of Marine Science and Technology, 2022)
Marine sediment quality at Vietnam’s coastal monitoring stations in 2020 has an average ecological risk impact, with an average SQG-Q index of 0.16. 4-Four out of 24 stations have sediment quality with zero ecological risk impact, including Bach Long Vi, Thuan An, Phan Thiet, and Sa Huynh stations. The remaining stations (20/24 stations) have sediment quality with moderate ecological risk impact. The SQG-Q indices in 2020 and 2019 tend to decrease compared to 2018 and 2017.